(3QSGdI SfO Hf Ydi aj GdbWhYs ((3YHOGdQMef Hf YeQ GdfGSN s)
(3ChdgG (B:s
(3bWhY RMd OQLJg ebGHdJg JQHjYG s
(3BNQgG (B:s
(3de jSde UGMHgG ef GdOaf hGdMHS ai eWehQI s
(3Vef eLehY , JQJjHgG (B: (3GdNGeSs
(3HgG fXGe GdJYbjHIs
(3ai fgGjJgG aGFOI ai GdMce Ydi GdgGeGJ hHYV LOGhd Ydi Pdcs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3Gdadcs